Sosialisasi Gerakan Literasi Anak : Upaya Peningkatan Minat Baca di RT 5 Batang Kabung Ganting Padang - Ahmad Fauzi; Nurul Suci Rahmadhani; Zahara Erita; Yulia Hanoselina (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The low interest in reading among children in Indonesia is a serious challenge in developing quality human resources in the future. A culture of literacy that has not been formed since early childhood has an impact on the weakness of children's critical thinking, analytical skills, and imagination. This article aims to examine various approaches to child empowerment in increasing interest in reading and literacy through literature studies. Several strategies analyzed include reading corners, school literacy movements, family-based reading programs, and creative approaches such as storytelling methods and the use of digital media. The results of the review show that a participatory approach that actively involves families, schools, and communities has proven to be more effective in increasing children's interest in reading and fostering sustainable literacy habits. In addition, the provision of relevant, varied, and enjoyable reading media for children is an important factor in strengthening a reading culture. Cross-sector synergy is needed to create a conducive literacy ecosystem from an early age.